(3GdeYQH GdeHjf YeG JVefg GdCfjS GdeWQH hQhVI GdfSQjfs - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s ((3YHjOQHg CHj GdbGSe Hf YHOGdQMef GdbGSe s)
(3ChdgG (B:s
(3hHYO , gPG JdNjU eYQH YeG ETJed Ydjg GdGfjS GdeWQH ai CNHGQ aGS hedhc GdeZQH , HjO Gfi PjdJg RjGOI ddJYjjf HeG GSJCKQJ Ydjg QhVI GdfSQjf ef edhc Hfi eQjf s
(3BNQgG (B:s
(3BNQ eG bUOfG LeYg djchf NJGeg eSckG hhbY GdaQGZ ef LeYg bHd UdGI GdLeYI ddjdI HbjJ ef QHjY GdChd SfI SHY hJSYjf hCda hUdGI Gddg hSdGeg Ydi fHHjg NGJe GdeQSdjf s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B145s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B684 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B403 s
Keywords: (3GdJGQjNs